Preliminary investigations of pathogenic variability expressed by Isariopsis griseola - Álvarez Ayala, G.; Schwartz, Howard F. (1979)
Investigations were conducted at CIAT to develop methodology required to evaluate resistance to Isariopsis griseola inherent in bean germplasm and breeding progeny. Abundant sporulation by the pathogen has been achieved by growing isolates in the lab. on V-8 medium incubated at 19 degrees Celsius in darkness for 10 days. Conidia are harvested in a water suspension from petri plates by rubbing the colony surface with a soft brush or thin wire. Inoculum concn. is adjusted to 2 x 10(4) conidia/ml. The following glasshouse inoculation procedures have been utilized: (1) rubbing leaf surfaces with cheesecloth soaked with a conidial suspension, (2) immersing leaf blades in a conidial suspension, and (3) spraying the conidial suspension onto leaves. The latter method has proven to be most reliable and practical to evaluate large nurseries. Inoculated plants are incubated in a large moisture chamber at 19-22 degrees Celsius for 6-8 days or until symptoms appear. Evaluations are based upon the leaf area expressing lesions, lesion size, and frequency/unit area. (CIAT)